PENGARUH HARGA JUAL DAN PROMOSI TERHADAP VOLUME PENJUALAN RELL PANCING VIKING 5000 SERIES 5080 PADA TOKO RAJA PANCINGLAHAT (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
The results of the discussion obtained the value of Y = 161.135 + 0.010 + 5.580. Results of discussion obtained value Y = 161.135 + 0.010 + 5.580. Constant value of 24, 683 means if the independent variables are ignored then the value of the variable sales volume (Y) of 161.135. The variable value of Work Planning (X1) is 0,010 which means if the variable of selling price (X1) is increased by 0,010 it will increase variable of sales volume (Y) equal to 0,010. The value of the Promotion variable (X2) is 5,580 which means if the Promotion (X2) variable is increased by 5,580 it will increase the sales volume volume (Y) by 5,580.The value of the terminated coefficient is 0.983 or 98.3%, this means that the selling price and promotion have a contribution to the sales volume variable of 98.3% and the remaining 1.7% is influenced by other factors not examined by the author. The results of the test together obtained the selling price variable (X1), and promotion (X2), having a joint effect on the sales volume variable (Y).The partial test shows that the selling price (X1) has a significant effect on increasing sales volume (Y) while the Promotion variable (X2) has a significant effect on the sales volume variable (Y).